Impact of COVID-19 restrictions on carers of persons with dementia in the UK: a qualitative study. (5th July 2021) - Sriram, Vimal; Jenkinson, Crispin; Peters, Michele
Abstract: Background: informal carers provide the majority of the support for persons with dementia living at home. Restrictions imposed due to COVID-19 have had a profound impact on the daily life of the entire population. This study provides insight into the impact of these restrictions on carers of people with dementia living at home. Design: qualitative semi-structured interviews. Participants: purposive sample of carers who provide at least 10 hours of care a week for the person with dementia living at home. Setting: UK. Results: twenty-three carers were interviewed, and thematic analysis identified three main themes—Changes to daily life, impact on carer health and wellbeing and reduced support from health and social support networks. The results highlight the impact of restrictions imposed on daily life and routines due to the pandemic, wellbeing of carers, reduced social support, lack of access to health and care professionals and respite for carers. The restrictions have had negative consequences on carers' wellbeing, and they have experienced difficulties in accessing formal care services and respite care. Conclusion: carers attempt to continue to provide physical, emotional and practical support for persons with dementia in the community throughout the COVID-19 restrictions. To prevent a future carer crisis, carers need better support systems including formal carer services, telecare solutions that work for them and additional support for respite, as the restrictions from this pandemic continue.